Distribution of mineral nitrogen in long-term conservation agriculture under semi-arid condition - YADAV, SURYA P; KUMAR, SARVENDRA; DAS, T K; PURAKAYASTHA, T J; SHARMA, V K; BHATTACHARYYA, R; G, ROSIN K; VISHWANATH, VISHWANATH (The Indian Journal of Agricultural Sciences, 2021)
Depthwise and temporal distribution of soil nitrogen release was carried out in pigeon pea [Cajunus cajan (L.) Millsp.] under conservation agriculture (CA) experiment (since 2010) during kharif 2019-20. The treatment includes conventional tillage (CT) and zero tillage (ZT), which includes: permanent narrow bed (PNB); PNB with residues of previous crop (PNB+R); permanent broad bed (PBB), PBB with residues (PBB+R), flat bed (FB) and FB with residues (FB+R). Soil samples were collected at different stages; pre-flowering, flowering, pod filling and harvest of pigeon pea from two depths (0-15 and 15-30 cm). Adopting CA practices increased NH4-N, NO3-N and mineral N over without CA plots irrespective of crop growth stages and depth of soil. As soil depth increases, NH4-N, NO3-N and mineral-N decreased and the reduction was more under CT and ZT without residues retained plots. The maximum NH4-N was observed at the flowering stage followed by pod filling > pre-flowering > harvest stage in 15 cm soil depth. The average NO3-N decreased from pre-flowering (34.3 mg/kg) to flowering (28.7 mg/kg) and increased at the pod filling stage (33.7 mg/kg). Among all treatments, PBB+R recorded significantly higher NH4-N, NO3-N, and mineral-N. In nutshell, adopting CA practices (PBB+R) may be a viable option for enhancing N availability, especially in semi-arid and arid conditions where N is always a limiting factor for crop growth and yield.